NILAI-NILAI ETIKA DALAM SERAT WURUK RESPATI - Sumiyardana, Kustri (Fakultas Ilmu Budaya Universitas Diponegoro, 2012)
Serat Wuruk Respati is one text inherited from traditional Java ancestors containing about moral didactic. One is about ethics. However, as of old works the text using archaic language so inclined elusive. To solve the problems analysis can use literary hermeneutic theory. Having performed the interpretation of this text, it may be known that kind of ethics taught is on encountering leader, social ethics, domestic ethics, ethics encountering brothers, parents, and teachers, as well as ethics in science and ethics to be a rich man. All these ethics contain two kinds of principles, these are harmony principles and respect principles.